ORGANISATION OF EMOTIONAL INTELLIGENCE DEVELOPMENT PROGRAMME IN THE EDUCATIONAL PROCESS AND PROFESSIONAL ACTIVITIES IN STEM FIELDS - Asadova, Nazrin (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Emotional intelligence plays a critical role in enhancing academic performance and professional success, particularly within STEM education and careers, by improving skills important for these fields. The purpose of the study is to determine the impact of the author's programme on the development of emotional intelligence in students and employees of professional institutions. The research methodology included an experiment involving assessing emotional intelligence and 200 participants from two universities (Baku State University and Azerbaijan State University of Oil and Industry) and two organisations (Baku Youth Centre and ASAN Service). The results showed that the experimental group under the innovative programme significantly improved emotional competence metrics compared to the control group. The participants of the experimental group demonstrated better emotional management skills, increased empathy and more effective interaction in a professional environment. Participants in the programme also increased their capacity for self-reflection and awareness of emotional processes. The analysis of the programme revealed its effectiveness and opportunities for further use in educational and professional activities. The study also highlighted the need for further training and programmes to support the development of emotional competence in educational and professional institutions. A prominent result of the study was the recommendation to implement similar programmes to improve emotional competence in educational and professional environments, as they contribute not only to personal growth but also to the overall performance of participants. In order to improve academic and professional outcomes, this study takes a unique approach to fostering emotional intelligence in STEM education and professional settings.